Alternative Argets Within the Endocannabinoid System for Future Treatment of Gastrointestinal Diseases - Rudolf Schicho; Martin Storr (Canadian Journal of Gastroenterology)
Many beneficial effects of herbal and synthetic cannabinoids on gut motility and inflammation have been demonstrated, suggesting a vast potential for these compounds in the treatment of gastrointestinal disorders. These effects are based on the so-called ‘endocannabinoid system’ (ECS), a cooperating network of molecules that regulate the metabolism of the body’s own and of exogenously administered cannabinoids. The ECS in the gastrointestinal tract quickly responds to homeostatic disturbances by de novo synthesis of its components to maintain homeostasis, thereby offering many potential targets for pharmacological intervention. Of major therapeutic interest are nonpsychoactive cannabinoids or compounds that do not directly target cannabinoid receptors but still possess cannabinoid-like properties. Drugs that inhibit endocannabinoid degradation and raise the level of endocannabinoids are becoming increasingly promising alternative therapeutic tools to manipulate the ECS.